2014
DOI: 10.1186/1756-3305-7-399
|View full text |Cite
|
Sign up to set email alerts
|

Avian roosting behavior influences vector-host interactions for West Nile virus hosts

Abstract: BackgroundExtensive work has shown that vectors almost never feed at random. Often, a subset of individual hosts and host species are fed on much more frequently than expected from their abundance and this can amplify pathogen transmission. However, the drivers of variation in contact patterns between vectors and their hosts are not well understood, even in relatively well-studied systems such as West Nile virus (WNV).MethodsWe compared roosting height and roost aggregation size of seven avian host species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 53 publications
(91 reference statements)
1
26
0
Order By: Relevance
“…Third, feeding on grackles may be hazardous to mosquito survival, presumably through grackle defensive behaviors such as consumption of host-seeking mosquitoes. Fourth, the high density of birds within a communal grackle roost may reduce the local vector-host ratio and therefore lower virus amplification potential within the roost site (Janousek et al 2014). Lastly, the additional species that often roost together with grackles (such as doves, starlings, and other blackbird species) may dilute the force of transmission within a grackle roost compared to single-species communal roosts like those of the house sparrow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, feeding on grackles may be hazardous to mosquito survival, presumably through grackle defensive behaviors such as consumption of host-seeking mosquitoes. Fourth, the high density of birds within a communal grackle roost may reduce the local vector-host ratio and therefore lower virus amplification potential within the roost site (Janousek et al 2014). Lastly, the additional species that often roost together with grackles (such as doves, starlings, and other blackbird species) may dilute the force of transmission within a grackle roost compared to single-species communal roosts like those of the house sparrow.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, this high density of hosts reduces the vector host ratio and ostensibly makes it more difficult for an infectious mosquito to make contact with a susceptible amplifier, or for an uninfected vector mosquito to make contact with an infectious bird (Janousek et al 2014). Mathematical modeling has demonstrated that reducing the vector-host ratio effectively reduces the force of the epidemic wave for WNV, which would result in fewer infected mosquitoes and lower transmission risk to humans (Magori et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While we acknowledge that these variables do not represent the totality of habitat variation along the rural-to-urban gradient, these land cover metrics have been shown to be predictive of avian nest success (canopy cover and impervious surface, Ryder et al, 2010), adult survival (impervious surface, Evans et al, 2015), and community composition (impervious surface, Evans, 2015). All spatial analyses were carried out in R using packages raster (Hijmans, 2015) and sp (Pebesma and Bivand, 2005). We calculated the proportional cover of impervious surface and canopy within a 3 脳 3 cell neighborhood moving window (for R code used throughout this manuscript, see Supplementary Material).…”
Section: Methodsmentioning
confidence: 99%
“…17 Finally, postbreeding dispersal and migration can influence contacts between hosts and vectors that affect disease transmission. 18,19 Co-circulation of pathogens (broadly defined here as the transmission of two or more pathogens in the same population at the same time) can have important implications for patterns of infection. Indeed, co-circulation is a critical factor permitting direct and indirect interactions among pathogens.…”
Section: Introductionmentioning
confidence: 99%